The Case for Microcredit: Does It Improve Maternal and Child Health and Wellbeing? - Madhurima Sarkar; Muhiuddin Haider (Intelektual Pustaka Media Utama, 2014)
It is possible to achieve the above development goals, if disposable income, especially of the poor, is increased. A joint research project in Bangladesh was initiated by BRAC and ICDDR,B to evaluate the extent to which socioeconomic development engineered through microcredit might enhance maternal and child health programs and to determine the impact of rural community development programs on community well-being. We conducted a systematic review on BRAC-ICDDR,B Joint Research Project Working Paper Series. The series contained 32 working papers out of which we only selected papers that examined or had references to maternal and child health (n=13). We developed a checklist based on the Transparent Report of Evaluations with Nonrandomized Designs (TREND) criteria. The BRAC papers show promising positive linkages between implementation of microcredit programs in rural areas and (1) increase in income, (2) increase in health status and (3) improvement in women’s health. The assumption that increasing women’s empowerment through income and education leads to improvements health and survival is referred a number of times in the BRAC studies, however, this assumption has not been tested in well controlled intervention studies and further independent research needs to be conducted in order to test the hypotheses set out by the BRAC papers. The data from BRAC is a unique opportunity to examine pre and post intervention of the impact of microcredit and such data sets can provides researchers with the prospect of conducting continuous rigorous research in the country.